New Concepts in the Management of Acute Myocardial Infarction - Hafizullah, Muhammad (Journal of Postgraduate Medical Institute, 2011)
Management of acute myocardial infraction is individualised to the demands of the patient. In general, pain is alleviated, hypoxaemia corrected and physical activity curtailed. Early detection of arrhythmia and correction by drugs or D.C. conversion has improved in-hospital mortality. Left ventricular failure and cardiagenic shocks adversely effect the prognosis and merit early treatment. Recently attempts have been made to contain myocardial infarct size by either reducing oxygen metabolic demand or increasing perfusion, by employing drugs of surgical techniques. Secondary prevention entails correction of risk factors and use of beta blockers. By-pass surgery is indicated in symptomatic patients.